Idiopathic thrombocytopenia, initial illness and long term follow up. Issue 4 (April 1984) - Walker, R W; Walker, W
Abstract : One hundred and eighty one children with thrombocytopenia for which no cause could be found have been studied. One patient died with severe bleeding possibly from disseminated intravascular coagulation and one developed cerebral haemorrhage, both within two weeks of onset. Ninety one per cent of the 135 with acute disease but only 36% of those with chronic disease remitted spontaneously. Twenty per cent of spontaneous remission occurred more than one year after onset. Six patients have run an intermittent course for 10 to 20 years. Four patients have had symptomless thrombocytopenia for between 10 and 30 years. Of 32 children treated by splenectomy 24 maintained normal platelet values thereafter. One boy died from pneumococcal septicaemia two years after splenectomy but he had not received prophylactic penicillin. One hundred and fifty eight patients were followed up 3 to 37 years (mean 16.4 years) after onset. None who recovered spontaneously or after splenectomy had had further bleeding problems. No patient nor immediate relative had developed other autoimmune disease. We consider that a short course of corticosteroids immediately after diagnosis is justified in all cases even though we cannot produce proof that it influences the course of the disease. We do not accept any place for long term immunosuppressant treatment.